Changes to sleep patterns and insomnia symptoms following cognitive behavioural therapy for anxiety disorders in adolescents - Sukiennik, A; Waite, P; Orchard, F; Percy, R (Cambridge University Press, 2024)
Background: It is unclear whether treatment for an anxiety disorder improves sleep. This study examined baseline sleep characteristics of adolescents with an anxiety disorder, comparing weekdays and weekends, and whether there were significant improvements in sleep following cognitive behaviour therapy (CBT). Aims: To improve our understanding of sleep problems in adolescents with an anxiety disorder and examine whether CBT for the treatment of the anxiety disorder improves sleep. Method: Data was gathered from 179 participants with an anxiety disorder (11–17 years old) who had previously engaged with the out-patient child and adolescent mental health service. Baseline self-report measures of anxiety and depression symptoms, sleep patterns and experiences of insomnia were examined. Of this group, 135 participants had baseline data. A subset (n=73) had outcome data, which was used to examine changes in sleep following CBT. Results: At baseline, adolescents reported significantly less total sleep and more night-time waking on weekdays than weekends. Following treatment for their anxiety disorder, adolescents’ weekday sleep patterns significantly improved for sleep onset latency and total sleep time, whereas weekend sleep patterns only showed improvements for sleep onset latency. No significant improvements were reported for symptoms of insomnia. Conclusions: The study relied upon subjective measurement of sleep and there was no control group; however, the findings provide promising results that CBT for adolescent anxiety disorders can improve some sleep problems. Further research is needed to understand discrepancies between subjective and objective sleep, and to explore avenues for the delivery of support for sleep problems.